The quasar main sequence and its potential for cosmology. Issue Volume 15:Issue S356(2019) (October 2019) - Marziani, Paola; Dultzin, Deborah; del Olmo, Ascensión; D'Onofrio, Mauro; de Diego, José A.; Stirpe, Giovanna M.; Bon, Edi; Bon, Natasa; Czerny, Bożena; Perea, Jaime; Panda, Swayamtrupta; Loli Martinez-Aldama, Mary; et al.
Abstract: The main sequence offers a method for the systematization of quasar spectral properties. Extreme FeII emitters (or extreme Population A, xA) are believed to be sources accreting matter at very high rates. They are easily identifiable along the quasar main sequence, in large spectroscopic surveys over a broad redshift range. The very high accretion rate makes it possible that massive black holes hosted in xA quasars radiate at a stable, extreme luminosity-to-mass ratio. After reviewing the basic interpretation of the main sequence, we report on the possibility of identifying virial broadening estimators from low-ionization line widths, and provide evidence of the conceptual validity of redshift-independent luminosities based on virial broadening for a known luminosity-to-mass ratio.